Facilitating or getting in the way? The effect of clinicians' knowledge, values and beliefs on referral and participation. (July 2016) - Gallagher, Robyn; Neubeck, Lis; Du, Huiyun; Astley, Carolyn; Berry, Narelle M; Hill, Martha N; Clark, Robyn
Background: Despite the compelling evidence of the benefits of cardiac rehabilitation (CR) on risk factor modification, quality of life and mortality reduction, a significant proportion of eligible patients are not referred or do not participate. Factors influencing CR referral and participation are complex and are likely patient, referral system and clinician-related. Little is known about clinician-related factors, which include attitudes, values and beliefs towards CR, or how these factors affect patient referral and attendance. This review examines the current evidence in the literature in relation to clinicians' attitudes, values and beliefs about CR. Methods: A review of the literature was conducted on studies in relation to clinicians' attitudes, values and beliefs toward CR. An expert consensus methodology was used to develop the concepts presented in this paper. Results: Besides guidelines, a range of other factors influence clinicians' view about CR. This review suggests that clinicians lacking cardiac qualifications may have limited knowledge and awareness of CR and its benefits. Low agreement among clinicians on who is more likely to benefit from CR was also identified. Clinicians' personal lifestyle and health belief, the availability and quality of local the CR programme, and the lack of a standard administrative process of referral can also hinder the referral of patients to CR. Conclusions: Clinician-related factors are important to consider in relation to CR referral and participation. Education for clinicians, discussion of local services and the support of an efficacious system at programme and organisation levels are essential.